WHY BETA-BLOCKERS ARE NOT PRESCRIBED TO PATIENTS WITH HEART FAILURE AND HOW TO IMPROVE IT? - S. N. Tereshchenko; I. V. Zhirov (Столичная издательская компания, 2016)
Aim. To determine indications for differential prescription of beta-blockers in patients with chronic heart failure (CHF) and to study efficacy and safety of beta-blockers therapy.Material and Methods. Patients (n=90; 55.6% of men; aged 64.7±1.9 y.o.) with CHF class 3-4 NYHA of ischemic and non-ischemic etiology with inadequate treatment with beta-blockers were included in the study. Patients were randomized into 3 groups depending on received beta-blocker: group 1 (n=30) - bisoprolol, group 2 (n=30) - carvedilol, group 3 (n=30) - nebivolol. Study duration was 6 months. Clinical examination (physical, laboratory and instrumental tests) and assessment of the adverse events was performed at baseline and after 6 months. Multiple regression analysis was performed to determine the probability of efficiency achievement by using different parameters (target heart rate, mortality, side effects, hospitalization, 6-minute walk test, left ventricle ejection fraction (LV EF), glomerular filtration rate).Results. Significant increase in LV EF was found: in group 1 from 32.4±6.1 to 47.2±4.1% (p=0.049); in group 2 from 31.3±8.4 to 46.5±4.2% (p=0.047); in group 3 from 30.3±6.9 to 46.8±4.0% (p=0.043). Class NYHA decreased in group 1 from 3.5±0.5 to 2.3±0.3 (p=0.044); in group 2 from 3.4±0.6 to 2.1±0.2 (p=0.045) and in group 3 from 3.6±0.4 to 2.4±0.4 (p=0.038). The hospitalization rate due to heart failure decompensation was 16.7, 16.7 and 13.3%, respectively. Mortality in groups during 6 months was 6.7, 0.0 and 3.3%, respectively. The efficacy of CHF therapy with betablockers depended on comorbidity and demographic characteristics. The highest refractoriness to CHF therapy was in patients with chronic kidney failure, atrial fibrillation and anemia (odds efficiency was 2.2, 2.9 and 3.1%, respectively). Bisoprolol was the most effective beta-blocker for the CHF patients treatment according to the majority of dependent variables in multiple regression analysis (p=22.13 vs. 20.66 for carvedilol and 18.69 for nebivolol).Conclusion. A differentiated approach to the beta-blocker prescription depending on the initial clinical and demographic patient characteristics can improve efficacy of the CHF treatment.